Bibliometric Analysis on the Risks of Oral Cancer for People Living with HIV/AIDS - Luana Kelle Batista MOURA; Mitra MOBIN; Francisca Tereza Coelho MATOS; Thiago Lima MONTE; Eliana Campelo LAGO; Carlos Alberto Monteiro FALCÃO; Maria Ângela de Arêa Leão FERRAZ; Tanit Clementino SANTOS; Fabrício Ibiapina TAPETY; Carla Maria de Carvalho Leite Leal NUNES; Laelson Rochelle Milanês SOUSA (Tehran University of Medical Sciences, 2017)
Bibliometric Analysis on the Risks of Oral Cancer for People